(3GdGMJLGL Ydi Cgd GddLGLs - (3YR GdOjf CMeO Hf Ydj Hf CHj WGdH, CHh efUhQ GdWHQSj,J (B560 (3g` s ((3GHf YHOGdhGMO GdHTQj s)
(3ChdgG (B:s
(3Ke Ef GdPi OYGfi Edi JCdja gPG GdcJGH YOhd LeGYI ef GdCUMGH aQCjJ Yed cJGH jMJhi Ydi PcQ Led ef eMGhQJge ai GdaQhY s
(3BNQgG (B:s
(3hgPg aVjdI JRjO Ydi GdaVGFd hGdMeO ddg QH GdYGdejf hGdUdGI Ydi NjQ Ndbg eMeO hqGdg GdWGgQjf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B31s
Keywords: (3GdJhMjO hGdedd hGdfMds